Safety in the Agricultural Mechanics Laboratory: A Needs Assessment of Tennessee School-Based Agricultural Educators - Saucier, Ryan G.; McKim, Billy R. (Journal of Agricultural Systems, Technology, and Management, 2014)
Accidents occur in all school-based agricultural education laboratories. The extent of these accidents varies by the situation, the individuals involved, and the safety protocols in place. However, it is a teacher’s responsibility to limit these accidents and provide a safe learning environment for student academic mastery (Phipps, Osborne, Dyer, & Ball, 2008). According to a review of literature, in many states, researchers have noted that agricultural teachers require some iteration of professional development in the area of safe agricultural mechanics laboratory management. This study investigated the agricultural mechanics laboratory safety professional development needs of Tennessee school-based agricultural educators who teach in and manage an agricultural mechanics laboratory. Data were collected with a web-based questionnaire designed to identify teachers’ perceptions of importance and their perceived ability to complete 70 selected agricultural mechanics laboratory competencies. The Borich (1980) needs assessment model was used to assess and evaluate the in-service needs of the teachers concerning laboratory safety. Results indicated Tennessee teachers had in-service needs in 13 of the 14 laboratory safety competencies with the greatest need concerning administering first aid. The researchers recommend that professional development opportunities be developed and offered to teachers concerning this critical need area, be delivered in formats conscious of teachers academic schedules, and in a format that reaches the most people, possibly in a web-based format.